PEMBERDAYAAN KELOMPOK WARUNG SOTO BANJAR DALAM MASA NEW NORMAL - Imelda, Sri; Rofi'i, Rofi'i; Huwaida, Hikmayanti; Anisari, Rezky (Jurnal IMPACT: Implementation and Action, 2020)
New normal as a new way of life in the midst of the coronavirus pandemic whose recovery rate is increasing. New normal is an accelerated step in the handling of Covid-19 in the field of health, social, and economic. Organizing community empowerment program for Warung Soto Banjar Group in The New Normal Period. This activity was held with Soto Rina Group Partners. The purpose of this community service: 1) the use of health protocol; 2) use of masks; 3) the use of sterilized cash; 4) open a soto stall; 5) increase sales; 6) body temperature gauge; 7) keep your distance at Warung Soto Rina. The method used in community service in the Community Empowerment Program scheme is training. This training was facilitated by the Service Team, the pattern applied consisted of: 1) lectures, this model participants were given material about Covid 19 and its way of transmission, new normal, and health protocols in the business place; 2) sharing experience, this model encourages trainees to tell various issues and cases, as well as the settlement strategies used; and 3) discussions, this model is used to stimulate participants to understand and resolve a given case. The results of devotion contribute to the target audience: On-site health protocols are implemented during the new normal period. Sales of Warung Soto Banjar Rina increased.